A pilot study on mindfulness based stress reduction for smokers - Baker Timothy B; Bonus Katherine A; Fleming Michael F; Davis James M (BMC, 2007)
Abstract Background Mindfulness means paying attention in the present moment, non-judgmentally, without commentary or decision-making. We report results of a pilot study designed to test the feasibility of using Mindfulness Based Stress Reduction (MBSR) (with minor modifications) as a smoking intervention. Methods MBSR instructors provided instructions in mindfulness in eight weekly group sessions. Subjects attempted smoking cessation during week seven without pharmacotherapy. Smoking abstinence was tested six weeks after the smoking quit day with carbon monoxide breath test and 7-day smoking calendars. Questionnaires were administered to evaluate changes in stress and affective distress. Results 18 subjects enrolled in the intervention with an average smoking history of 19.9 cigarettes per day for 26.4 years. At the 6-week post-quit visit, 10 of 18 subjects (56%) achieved biologically confirmed 7-day point-prevalent smoking abstinence. Compliance with meditation was positively associated with smoking abstinence and decreases in stress and affective distress. Discussions and conclusion The results of this study suggest that mindfulness training may show promise for smoking cessation and warrants additional study in a larger comparative trial.